Time Spent on Daily Activities and Its Association with Life Satisfaction among Czech Adolescents from 1992 to 2019 - Kvasková, Lucia; Rečka, Karel; Ježek, Stanislav; Macek, Petr (International journal of environmental research and public health, 2022)
Life satisfaction, an important precursor of adolescents' well-being, is linked to daily activities. Substantial changes have been noted in adolescents' daily activities over the years, raising the question of possible consequences for life satisfaction. This study aimed to explore changes in adolescents' life satisfaction and their time spent on daily activities (sleeping, engaging in sports, online gaming, school commuting, time spent at school) and further investigate the associations between adolescents' life satisfaction and these daily activities. The sample comprised 2715 adolescents from birth cohorts surveyed at four time points between 1992 and 2019. Participants were administered the Daily Activities Inventory and the Berne Questionnaire on Adolescents' Well-Being. Robust ANOVA with post hoc tests and spline regression were employed. We found cohort differences in sleep duration (8.6 h a day on average in 1992 and 7.5 in 2019). Sleep duration of 8 h and 1 h of sports activities had a beneficial effect on life satisfaction, while more than 1 h of online gaming had a negative impact. Neither school attendance nor commuting to school was associated with adolescents' life satisfaction. The results of this study can inform public-health policies to promote sleeping and sports habits in adolescence.
Keywords: Surveys and Questionnaires; adolescents; spánek; Humans; daily activities; Schools; osobní uspokojení; birth cohorts; lidé; průzkumy a dotazníky; sleep duration; Sleep; sports; life satisfaction; školy; Adolescent; time spent at school; Czech Republic; leisure; online gaming; Personal Satisfaction; Česká republika; school commuting; mladiství